2019
DOI: 10.1021/acs.jpcc.9b08066
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Theoretical Investigation of the Origin of Magnetic Anisotropy in Pentagonal Bipyramidal Isothiocyanato Co(II), Ni(II), and Fe(III) Complexes with Quaternary-Ammonium-Functionalized 2,6-Diacetylpyridine Bisacylhydrazone

Abstract: The magnetic anisotropy in pentagonal bipyramidal complexes of Co(II) (1 and 2), Fe(III) (3 and 4) and Ni(II) (5) with 2,2′-[2,6-pyridinediylbis(ethylidyne-1-hydrazinyl-2ylidene)]bis[N,N,N-trimethyl-2-oxoethanaminium] equatorial ligand and isothiocyanato axial ligands has been investigated by magnetic susceptibility measurements, powder X-band EPR spectroscopy, Mössbauer spectroscopy, ab initio, and LFDFT calculations. The studied complexes display three distinct types of magnetic anisotropy. Co(II) complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 102 publications
(280 reference statements)
2
21
0
Order By: Relevance
“…Most of the seven‐coordinate Co II complexes are stabilised in pentagonal bipyramidal (PBP or D 5 h symmetry) geometry or distorted PBP geometries. To mention [Co‐(H 2 DAPBH)(H 2 O)(NO 3 )]NO 3 ( 1 ) [18] (H 2 DAPBH=2,6‐diacetylpyridine bis‐benzolylhydrazone), [Co(H 2 daps)(MeOH) 2 ] ( 2 ) [19] (H 2 daps=2,6‐bis(1‐salicyloylhydrazonoethyl) pyridine) and [Co(H 2 L)(NCS) 2 ](SCN) 2 ( 3 ) [20] (H 2 L=2,2′‐[2,6‐pyridinediylbis(ethylidyne‐1‐hydrazinyl‐2‐ylidene)]bis[ N , N , N ‐trimethyl‐2‐oxoethanaminium]) complexes possess D values of +35(31) cm −1 , +38(43) cm −1 and +41(30) cm −1 , respectively, as revealed from NEVPT2 calculations and SQUID data (see Figure 2 c–f). Ground state electronic configuration in these geometries can be represented by the d xz 2 d yz 2 dx2-y2 1 d xy 1 dz2 1 electronic configuration.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the seven‐coordinate Co II complexes are stabilised in pentagonal bipyramidal (PBP or D 5 h symmetry) geometry or distorted PBP geometries. To mention [Co‐(H 2 DAPBH)(H 2 O)(NO 3 )]NO 3 ( 1 ) [18] (H 2 DAPBH=2,6‐diacetylpyridine bis‐benzolylhydrazone), [Co(H 2 daps)(MeOH) 2 ] ( 2 ) [19] (H 2 daps=2,6‐bis(1‐salicyloylhydrazonoethyl) pyridine) and [Co(H 2 L)(NCS) 2 ](SCN) 2 ( 3 ) [20] (H 2 L=2,2′‐[2,6‐pyridinediylbis(ethylidyne‐1‐hydrazinyl‐2‐ylidene)]bis[ N , N , N ‐trimethyl‐2‐oxoethanaminium]) complexes possess D values of +35(31) cm −1 , +38(43) cm −1 and +41(30) cm −1 , respectively, as revealed from NEVPT2 calculations and SQUID data (see Figure 2 c–f). Ground state electronic configuration in these geometries can be represented by the d xz 2 d yz 2 dx2-y2 1 d xy 1 dz2 1 electronic configuration.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 99%
“…Multi‐configurational CASSCF/NEVPT2 calculations reveal that the ZFS arises dominantly from the first four spin‐allowed excited ligand‐field states and all four consist of different M L valued electronic transition (see Figure 2 a). [18–21] It was found that the axial ligand donor strength and the equatorial ligand symmetry plays a very important role in determining the magnitude of the D value in these type of complexes. Particularly as the major contribution to D arises from different M L level excitations, D is expected to be positive, and as the gap between the d xz /d yz to d xy /dx2-y2 decides the magnitude of D , it is expected to be only moderate.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 99%
“…The τ value of 0.36 calculated for 1, indicates that the irregular coordination geometry about Zn1 is 36% trigonally distorted square-based pyramidal. The greatest basal angles O1−Zn1−N1 and N2−Zn1−N5 are 149.20 (7) • and 127.42(10) • , respectively. The Zn1 is lifted out of the plane of the four in-plane ligand atoms (O1, N1, N2 and N5) by a distance ρ of 0.6091( 3 coplanar nature of metal-ligand system.…”
Section: Crystal Structures Of [Znl 1 (Ncs)2]2h2o (1) and [Zn(l 2 )2] (2) Complexesmentioning
confidence: 99%
“…Hydrazone ligands are one of the most important classes of flexible and versatile polydentate ligands which show very high efficiency in chelating various metal ions [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The coordination behavior of hydrazones is known to depend on the pH of the medium, the nature of the substituents and on the position of the hydrazone group relative to other moieties [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation